Jargon “HMI Bersuara” dan Tantangan Kepemimpinan Modern: Studi Kritis Atas Efektifitas dan Penerapannya - Dalimunthe, Ahmad Ridwan (Medan Resource Center, 2023)
This study aims to examine the effectiveness and challenges of implementing the 'HMI Bersuara' jargon in the leadership practice of the Islamic Student Association (HMI) and its impact on motivation, member performance, and organizational identity. Using a qualitative approach and a case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The results show that a deep understanding of the jargon correlates positively with member participation and motivation, and impacts individual and group performance. However, there are challenges in ensuring a uniform understanding among all members, as well as in managing internal conflicts and adapting to external changes. The practical implications of this study emphasize the importance of intensive and ongoing socialization to strengthen understanding and appreciation of organizational jargon in shaping a strong and effective organizational culture.